Melanomas prevent endothelial cell death under restrictive culture conditions by signaling through AKT and p38 MAPK/ ERK-1/2 cascades. (2nd October 2016) - Das, Asha M.; Pescatori, Mario; Vermeulen, Cindy E.; Rens, Joost A. P.; Seynhaeve, Ann L. B.; Koning, Gerben A.; Eggermont, Alexander M. M.; ten Hagen, Timo L. M.
ABSTRACT: Although melanoma progression and staging is clinically well characterized, a large variation is observed in pathogenesis, progression, and therapeutic responses. Clearly, intrinsic characteristics of melanoma cells contribute to this variety. An important factor, in both progression of the disease and response to therapy, is the tumor-associated vasculature. We postulate that melanoma cells communicate with endothelial cells (ECs) in order to establish a functional and supportive blood supply. We investigated the angiogenic potential of human melanoma cell lines by monitoring the survival of ECs upon exposure to melanoma conditioned medium (CM), under restrictive conditions. We observed long-term (up to 72 h) EC survival under hypoxic conditions upon treatment with all melanoma CMs. No such survival effect was observed with the CM of melanocytes. The CM of pancreatic and breast tumor cell lines did not show a long-term survival effect, suggesting that the survival factor is specific to melanoma cells. Furthermore, all size fractions (up to < 1 kDa) of the melanoma CM induced long-term survival of ECs. The survival effect observed by the < 1 kDa fraction excludes known pro-angiogenic factors. Heat inactivation and enzymatic digestion of the CM did not inactivate the survival factor. Global gene expression and pathway analysis suggest that this effect is mediated in part via the AKT and p38 MAPK/ ERK-1/2 signaling axis. Taken together, these data indicate the production of (a) survival factor/s (< 1 kDa) by melanoma cell lines, which enables long-term survival of ECs and promotes melanoma-induced angiogenesis.